A measurement model of lecturer's personality for public higher education institution in Malaysia - Mat, Norazuwa; Mat, Norsiah; Romli, Ruslan; Jusoff, Kamaruzaman; Dahlan, Noornina; Osman, Intan (Institute of Interdisciplinary Business Research, 2010)
Personality variables have always predicted important behaviors and outcomes. Personality research also receiving increasingly positive attention nowadays because personality plays an important role in the prediction of criterion, and an agreement among researchers that Five Factor Model (FFM) can serve as taxonomy for investigating personality to the related issues. Specifically, the personality of the lecturer can greatly influence the ratings of his/her effectiveness. This study considers the development and validation of a measurement instrument of personality based on lecturer's self-evaluation. The samples are drawn from lecturers in public higher education institution in Malaysia. Structural Equation Modeling (SEM) technique namely confirmatory factor analysis was used to examine the measurement model of personality. The results obtained indicate the existence of five dimensions namely extraversion, agreeableness, openness to experience, emotional stability and conscientiousness. The various tests employed show a reasonable degree of reliability and validity of the proposed scale. The reliabilities for the dimensions are as follows, .75,.73,.87,.85 and .97. The study concluded that the model is valid and reliable for samples in Malaysia.